ANALISIS RESEPSI KHALAYAK MENGENAI ORANG DENGAN GANGGUAN JIWA (ODGJ) PADA AKUN YOUTUBE MENJADI MANUSIA - Bestari Bioneva (2023)
Menjadi Manusia YouTube channel creates a form of caring for people with mental disorders (ODGJ) on its YouTube channel entitled "Stop Sebut Orang Gila, ODGJ Juga Manusia". The video attempts to present a picture of a social phenomenon, namely the wrong view of society towards people with mental disorders in Indonesia in terms of the stigma and discrimination that have been attached to people with mental disorders. This research tries to find out how audience reception, namely Youtube channel viewers, becomes human regarding the issue of stigmatization of ODGJ, find out the position of audience acceptance, and find out what factors are behind this audience reception. This study uses a qualitative approach, namely reception analysis. The results of the study show that the background owned by YouTube viewers of "Menjadi Manusia" influences their reception of the issue of stigmatization in people with mental disorders (ODGJ). The audience's reception was more influenced by factors namely education, knowledge of mental health issues (field of knowledge), and direct experience of interacting with ODGJ, as well as being a survivor of psychiatric disorders (field of experience). Interpretation of meaning is also the result of the learning process that is obtained by the audience from their environment, namely from their family and the media they consume. The experience of YouTube channel viewers being different human beings makes them interpret things differently.